How it all started : the history behind the way our world works today. (London : Reader's Digest, 2008)
The way we live in the modern era has its roots much further back in history. This title, crammed full of quirky facts and detailed analysis, explores the complex and fascinating political, social, religious and cultural factors that have made our world the way it is today.
Keywords: World history; Civilization -- History